2020
DOI: 10.1126/scisignal.abb5727
|View full text |Cite
|
Sign up to set email alerts
|

EGF promotes DKK1 transcription in hepatocellular carcinoma by enhancing the phosphorylation and acetylation of histone H3

Abstract: The protein Dickkopf-1 (DKK1) is frequently overexpressed at the transcript level in hepatocellular carcinoma (HCC) and promotes metastatic progression through the induction of β-catenin, a Wnt signaling effector. We investigated how DKK1 expression is induced in HCC and found that activation of the epidermal growth factor receptor (EGFR) promoted parallel MEK-ERK and PI3K-Akt pathway signaling that converged to epigenetically stimulate DKK1 transcription. In HCC cell lines stimulated with EGF, EGFR-activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Immunohistochemical staining was conducted as previously described (Niu et al, 2020). Briefly, tumors from the mice were dehydrated and embedded in paraffin after fixation with 4% paraformaldehyde.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…Immunohistochemical staining was conducted as previously described (Niu et al, 2020). Briefly, tumors from the mice were dehydrated and embedded in paraffin after fixation with 4% paraformaldehyde.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…In colon cancer SW480 cells, Genistein was found to affect histone H3 acetylation at the DKK1 promoter [ 69 ]. Additionally, Niu et al observed that epidermal growth factor (EGF) initiates DKK1 expression in HCC cells by increasing histone H3 acetylation through p300 [ 70 ] (Table 1 ). Together, these studies suggest that histone acetylation at the promoters of endogenous inhibitory molecules can promote expression of these gene to suppress Wnt/β-catenin signaling, which means that the deacetylation of histone at the promoters of these molecules is in favor of Wnt/β-catenin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…DKK1 is a secretory Wnt antagonist, and abnormal expression of DKK1 has become recognized as an important regulator of many human cancers. Some reports indicate that DKK1 is a tumour promoter in pancreatic cancer, oesophageal cancer, and hepatocellular carcinoma [ 54 , 55 ]. In contrast, DKK1 expression is downregulated in thyroid cancer [ 56 ], cutaneous squamous cell carcinoma [ 57 ], and breast cancer [ 58 ], suggesting that DKK1 may have a tumour suppressive effect.…”
Section: Discussionmentioning
confidence: 99%